Complex pollination of a tropical Asian rainforest canopy tree by flower‐feeding thrips and thrips‐feeding predators. Issue 11 (20th October 2016) - Kondo, Toshiaki; Nishimura, Sen; Tani, Naoki; Ng, Kevin Kit Siong; Lee, Soon Leong; Muhammad, Norwati; Okuda, Toshinori; Tsumura, Yoshihiko; Isagi, Yuji
Abstract : PREMISE OF THE STUDY: In tropical rainforests of Southeast Asia, a highly fecund thrips ( Thrips spp.) responds rapidly to the mass flowering at multiple‐year intervals characteristic of certain species such as the canopy tree studied here, Shorea acuminata, by feeding on flower resources. However, past DNA analyses of pollen adherent to thrips bodies revealed that the thrips promoted a very high level of self‐pollination. Here, we identified the pollinator that contributes to cross‐pollination and discuss ways that the pollination system has adapted to mass flowering. METHODS: By comparing the patterns of floral visitation and levels of genetic diversity in adherent pollen loads among floral visitors, we evaluated the contribution of each flower visitor to pollination. KEY RESULTS: The big‐eyed bug, Geocoris sp., a major thrips predator, was an inadvertent pollinator, and importantly contributed to cross‐pollination. The total outcross pollen adhering to thrips was approximately 30% that on the big‐eyed bugs. Similarly, 63% of alleles examined in S. acuminata seeds and seedlings occurred in pollen adhering to big‐eyed bugs; about 30% was shared with pollen from thrips. CONCLUSIONS: During mass flowering, big‐eyed bugs likely travel among flowering S. acuminata trees, attracted by the abundant thrips. Floral visitation patterns of big‐eyed bugs vs. other insects suggest that these bugs can maintain their population size between flowering by preying upon another thrips ( Haplothrips sp.) that inhabits stipules of S. acuminata throughout the year and quickly respond to mass flowering. Thus, thrips and big‐eyed bugs are essential components in the pollination of S. acuminata .